Subsidiarity principle: Its realization in self-government in Lithuania and Poland - Robert Gawłowski; Saulius Nefas; Krzysztof Makowski (Administrative Sciences, 2020)
Purpose: This paper analyzes the development of the concept of subsidiarity, its relationship with management theories and the implementation of the principle of subsidiarity in the context of local self-government in Poland and Lithuania by conducting comparative research. Design/methodology/approach: The research was conducted based on methods of desk research of scientific literature, analysis of documents and their content from the Lithuanian and Polish parliaments' commissions and using comparative approach methods. Findings: The research reveals the essential aspects of the concept of subsidiarity and the extent to which this principle is relevant in the work of the Committee on State Administration and Local Authorities of the Seimas of the Republic of Lithuania and Self-Government and Regional Policy Commission of the Sejm of the Republic of Poland in shaping the policy of self-government. The study demonstrates that subsidiarity principles are used in practice in a very incoherent way regarding public service regulations. Practical implications: The analysis is relevant, as an implementation of public policy in Lithuania and Poland increasingly calls for the integration of values into politics, which cannot be done without relying on certain principles. Research limitations: The generalizability of the results is limited by the number of parliamentary terms that have been taken into consideration. Originality/value: The originality of this paper lies within the context in which this study took place - an international comparison of Lithuanian and Polish concepts that is rarely taken into consideration in the scientific literature.
Keywords: 350; subsidiarity; self-government; public administration